Debt Forgiveness and Debt Relief for Covid-19 Economic Recovery Financed through GDP-Linked Sukuk - Mohamed, Hazik; Mobin, M. Ashraful (European Journal of Islamic Finance, 2020)
This paper proposes alternatives for governments to deal with the current pandemic crisis today. It suggests ways to deal with the increasing debt levels as a result of the fiscal stimulus issued to cushion the effects of a tremendous shock to the economy. Firstly, the paper proposes to protect the vulnerable group (based on debt-to-income ratio or its debt-servicing ability) through debt forgiveness and help SMEs through debt relief via debt restructuring for their outstanding loans. To finance this, we propose to convert the increased public debt from these initiatives into equity through a GDP-linked sukuk to stabilise a sovereign’s debt to GDP ratio. The repayment on these sukuk will be in proportion to the country’s GDP whereby the repayment automatically declines when growth is weak and increases when GDP is strong. In doing so, an anticipated deep recession caused by the global pandemic slowdown will makes it less likely to trigger a sovereign debt crisis. Secondly, such a strategy would provide the issuing government with economic reprieve when growth weakens and tax receipts decline. At the same time, investors can view these sukuk as an alternative asset class through exposure to the real economy, given the low interest rate environment. Both sides are incentivized by the debt-stabilising effects of issuance that would make sovereign defaults less likely and balance risk-taking.